Pengaruh Kesiapan Berubah dan Komitmen Organisasi Terhadap Perubahan Organisasi Badan Perencanaan Pembangunan Riset dan Inovasi Daerah Kabupaten Sragen - Afnan Nur Fadhilah; Putri Oktovita Sari (Indo Publishing, 2025)
This study aims to analyse the significant of the influence of readiness to change and organizational commitment on organizational change. The type of data used is quantitative, with primary data as the source. The sampling technique used is saturated sampling, with a total sample of 39 respondents who are employees of the Regional Development, Research, and Innovation of Sragen Regency BAPPERIDA. Data collection methods include questionnaires, observation, and literature study. The data analysis technique applied is multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The results of this study indicate that readiness to change has a significant effect on organizational change of Sragen Regency BAPPERIDA. Organizational commitment also has a significant effect on organizational change of Sragen Regency BAPPERIDA. The F-test results indicate a significance value (p-value) of 0.000 < 0.05, meaning that the model is appropriate in predicting the influence of readiness to change and organizational commitment on organizational change of Sragen Regency BAPPERIDA. The coefficient of determination analysis shows a value of 0.873, which means that the contribution of readiness to change and organizational commitment variables to organizational change at BAPPERIDA Sragen Regency is 87.3%, while the remaining 12.7% is explained by other variables.